Integrasi Nilai Islam untuk Membangun Karakter Profil Pelajar Pancasila di Sekolah Dasar - Vieto Budi Utomo; Adhy Putri Rilianti (Jurnal Pena Karakter : Jurnal Pendidikan Anak dan Karakter, 2022)
This research aims to integrate Islamic values ​​to build the character profile of Pancasila students in elementary schools. The method used in this research uses a library research method or approach. The results of this research show that the Pancasila student profile is one of the policies that supports the realization of national education goals and the continuation of character strengthening programs. The Pancasila student profile is the character and competency that Indonesian students must have. Through the application of the 6 dimensions of the Pancasila student profile, namely faith and devotion to God Almighty, global diversity, independence, mutual cooperation, critical thinking and creativity, it is hoped that the Indonesian nation will become intelligent individuals who have character and of course instill the values ​​contained in Pancasila. Through the integration of Islamic values, it is hoped that it will be able to build the character of the Indonesian people who are faithful and devoted to God Almighty.